2018
DOI: 10.1186/s13613-018-0427-1
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory changes of the inferior vena cava diameter predict fluid responsiveness in spontaneously breathing patients with cardiac arrhythmias

Abstract: BackgroundWhether the respiratory changes of the inferior vena cava diameter during a deep standardized inspiration can reliably predict fluid responsiveness in spontaneously breathing patients with cardiac arrhythmia is unknown.MethodsThis prospective two-center study included nonventilated arrhythmic patients with infection-induced acute circulatory failure. Hemodynamic status was assessed at baseline and after a volume expansion of 500 mL 4% gelatin. The inferior vena cava diameters were measured with trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(79 citation statements)
references
References 37 publications
1
75
2
1
Order By: Relevance
“…[ 12 , 13 ] Recently published studies have claimed that even in patients with spontaneous breathing, this value can help in determining the volume status. [ 14 ] Moreover, it has been reported that the absolute value of the IVC diameter can predict the volume status. [ 15 ] In trauma patients, the diameter of the IVC measured on a computed tomography (CT) scan has been reported to be associated with the prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…[ 12 , 13 ] Recently published studies have claimed that even in patients with spontaneous breathing, this value can help in determining the volume status. [ 14 ] Moreover, it has been reported that the absolute value of the IVC diameter can predict the volume status. [ 15 ] In trauma patients, the diameter of the IVC measured on a computed tomography (CT) scan has been reported to be associated with the prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Second, spontaneous breathing is difficult to standardize, and we hypothesized that premedicated patients without obvious signs of agitation (RASS≤1) and respiratory efforts constitute an adequate setting for IVC measurements. Our protocol tends to follow physiologic airway pressure changes but therefore differs from that of some cited studies, which chose forced deep inspiration [15] or sniffing [14] [16]. Additionally, our study, by its observational nature, is not entirely free from intergroup differences: patients in the CI+ group were slightly older than those in the CI-group (median 69 vs 61 years.).…”
Section: Discussionmentioning
confidence: 99%
“…However, a French center reported that parameters of high anesthesiological importance such as global left ventricular function, ventricular diameters, pericardial effusion or the diameter of the inferior vena cava were adequately evaluated by trainees who had taken part in a 12 hour learning program [9]. Concerning volemic status, the variability of the diameter of the inferior vena cava (IVC), which follows the respiratory cycle, is considered to be a valuable predictor of volume responsiveness in cases of circulatory failure in ventilated [10] [11] [12] [13] and spontaneously breathing patients [14] [15] even in the presence of nonfatal cardiac arrhythmias [16]. In these studies, clinically evident volume responsiveness was defined as an at least 10% increase in cardiac output in response to bolus fluid administration.…”
Section: Introductionmentioning
confidence: 99%
“…A decision algorithm was proposed to guide FR assessment in complex cases (Additional file 1). Only tests with a validated cutoff for a 10-15% increase in CO after a fluid challenge were allowed [13,14,17,33,34]. A detailed description of each used test including its cutoffs is presented in Additional file 2.…”
Section: Methodsmentioning
confidence: 99%
“…They allow to determine the position of the patient's heart on its systolic function curve. By applying the appropriate tests, FR can be assessed in a wide variety of clinical settings [16][17][18]. However, despite their relative simplicity, lack of cost, and side effects, the use of FR tests has not completely permeated into routine clinical practice [19,20].…”
Section: Introductionmentioning
confidence: 99%